Pengaruh Dukungan Sosial Teman Sebaya dalam Pemilihan Studi Lanjut pada Peserta Didik SMA Islam Al-Falah Kota Jambi - Hasanatul Arni Rangkuti; Rasimin Rasimin; Freddi Sarman; Muhammad Zulfikar (Journal on Education, 2023)
The purpose of this study was to measure the level of influence of peer social support in the selection of further study of students at Al-Falah Islamic High School, Jambi City. This type of research is quantitative research with an ex-post facto approach. The sample in this study was 150 students. Selection of the sample using simple random sampling technique. Data collection techniques used questionnaires and interviews while data analysis techniques used formula C, normality test, linearity test and simple regression analysis. The results of the study show that there is a significant influence between the X and Y variables. This effect is evidenced by the sig.0.05 value which indicates that there is an influence between variables. In addition, it is also evidenced by the r count value of 0.327 which is interpreted as quite strong, which means that students have the influence of peer social support in selecting further studies. The results of this study are expected to have implications for guidance and counseling for students, both in the field of personal guidance and the social field.